Correlation between Suicidal Ideation and Addiction to Various Social Media Platforms in a Sample of Young Adults: The Benefits of Physical Activity - Mendes, Liliana (2023)
The rise in suicide death rates has become a major public health concern, which has led to increased addiction to internet and social media platforms. Despite the limited research available on the relationship between suicidal ideation and addiction to social media such as Instagram and TikTok, this study aims to examine this connection. The study design is cross-sectional, quantitative, comparative, and correlational, with a quasi-experimental approach. The sample includes 315 young adults aged 20 to 30 who were surveyed through the administration of the Suicidal Ideation Questionnaire (SIQ) and the Social Media Disorder Scale-Short Form (SMDS-SF) surveys. The results showed differences in addiction levels based on the type of social media, specifically between TikTok and other social media platforms. The study found that female participants who engage in physical activity (PA) four times a week had lower levels of suicidal ideation than those who did not; there were no differences compared to male participants. This suggests that PA may be a potential strategy for preventing and reducing suicide-related phenomena. The results also indicate that addiction to social media was a statistically significant predictor of suicidal ideation, after controlling for gender and PA.